Fruit quality and volatile constituents of a new very early-ripening pummelo (Citrus maxima) cultivar ‘Liuyuezao’ - Pan, Tengfei; Kong, Lingchao; Zhang, Xinxin; Wang, Yanhui; Zhou, Jinyu; Fu, Zhijun; Pan, Heli; She, Wenqin; Yu, Yuan (Frontiers in Plant Science, 2023)
‘Liuyuezao’ (LYZ) pummelo (Citrus maxima) originated from a spontaneous bud sport on a ‘Guanxi’ (GXB) pummelo tree and was released as a new very early-season cultivar. The objective of this study was to present the sensory and nutritional profiles of LYZ fruits, and compare it with other major commercialized pummelo cultivars including GXB, ‘Sanhong’ (SH) and ‘Hongrou’ (HR). LYZ had higher contents of titratable acids, phenols, vitamin C and stronger antioxidant capacity but lower levels of soluble sugars, carotenoids and flavonoids when compared to the other pummelos. Moreover, a smaller number (49) and much less content (7.63) of fruit volatiles were detected in LYZ than in GXB, SH and HR. The relatively high levels of fructose and titratable acids and low levels of volatile compounds in LYZ mainly contributed to its sweet and mildly sour taste and moderate aroma of pummelo note. LZY is presented as an alternative pummelo cultivar with the potential for commercialization.